Brazilians’ perception regarding the use of generic drugs for hypertension and their equivalence relationship to reference drugs (Research, Society and Development, 2024)
To identify the degree of knowledge about the use of generic drugs of the antihypertensive class in two Brazilian municipalities and to correlate the sociodemographic profile and its comparison with the reference use. Observational research of descriptive and quantitative nature of participants who used generic Antihypertensive drugs. Data collection was done through an online questionnaire on Google Forms. The sociodemographic profile was (69.0%) female and (31%) male. The average age presented was 34. (62.0%) from the city of Santarém/PA, while (38.0%) from the city of Dourados/MS. Different professional categories, such as: Nurses, Pharmacists, Administrators and Physiotherapists added up (64.0%) to the prevalence of generic drug use. The average salary ranged from 3 to 5 thousand reais. When obtaining the medication (63.0%) obtained it without a prescription. (56.0%) receive information about the drug they would use, the quality of the drug and the need for use, but (44.0%) of the population left the consultation without proper information. (63.0%) of the research participants said the advertisement associated with the use of generics is not positive. As for non-adherence to the use of generic drugs, (50.0%) of the participants had no reason not to use the medication, while (12.0%) would only not use it due to commercial unavailability. The participants' perception of the use of generic drugs in relation to reference drugs is positive, the population showed a good level of knowledge, identifying generic drugs and accepting them.